2015
DOI: 10.1186/1471-2393-15-s2-s9
|View full text |Cite
|
Sign up to set email alerts
|

Counting every stillbirth and neonatal death through mortality audit to improve quality of care for every pregnant woman and her baby

Abstract: BackgroundWhile there is widespread acknowledgment of the need for improved quality and quantity of information on births and deaths, there has been less movement towards systematically capturing and reviewing the causes and avoidable factors linked to deaths, in order to affect change. This is particularly true for stillbirths and neonatal deaths which can fall between different health care providers and departments. Maternal and perinatal mortality audit applies to two of the five objectives in the Every New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
167
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(181 citation statements)
references
References 49 publications
7
167
0
7
Order By: Relevance
“…Perinatal mortality is an important indicator of maternal and child health because it reflects the socioeconomic conditions, reproductive health, and quality of care provided in the prenatal period, during labour, and to the newborn (1)(2) . Child mortality has dropped significantly around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal mortality is an important indicator of maternal and child health because it reflects the socioeconomic conditions, reproductive health, and quality of care provided in the prenatal period, during labour, and to the newborn (1)(2) . Child mortality has dropped significantly around the world.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Ghana also suggested that trainings to the health worker with follow up mechanism to ensure the quality of data can improve the further planning to achieve reduce the maternal mortality outcomes [21]. Kerber et al [22] stated that health workers are the main source of collecting data at every steps in health care system to identify the best practices and flaws and that leads to create responsibility based health system not only at managers level but also at other level to reduce the systemic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that audits and feedback can lead to quality improvement, (68) and positive effects have been observed on maternal health services in settings where the audit system is underpinned by a national framework with properly implemented feedback mechanisms, leadership both from committed health professionals and the ministry of health, an enabling legal framework, and a workplace culture which promotes learning. (69,70) Despite the link between maternal, fetal and neonatal mortality, perinatal reviews have not been as widely adopted as maternal death reviews. (70,71) A policy review found that of the 51 "Countdown to 2015 for Maternal, Newborn and Child Health" priority countries which had a policy for maternal death notification, only 17 had a similar policy for perinatal death reviews in 2014.…”
Section: Auditmentioning
confidence: 99%
“…(69,70) Despite the link between maternal, fetal and neonatal mortality, perinatal reviews have not been as widely adopted as maternal death reviews. (70,71) A policy review found that of the 51 "Countdown to 2015 for Maternal, Newborn and Child Health" priority countries which had a policy for maternal death notification, only 17 had a similar policy for perinatal death reviews in 2014. (70) Even in countries with a national policy on perinatal review, they are not necessarily implemented.…”
Section: Auditmentioning
confidence: 99%
See 1 more Smart Citation